The response of financial market indices to covid-19 pandemic - Atif Sattar Muhammad; Felix E.lJr. Arcilla; Muhammad Fahad Sattar (Financial Studies, 2020)
Indices are a crucial part of the global investment business. The main objective of the study is to determine the impact of COVID-19 on stock indices to analysefinancial markets' response. The study applied a log-log simple regression model to analysethe effects of COVID-19 on stock indices by using EVIEWS. The result shows that COVID-19 has a substantial negative impression on market indices. In addition, critical analysis findings are benchmark index like the S&P 500, and Dow Jones Industrial Average has plummeted. On the other hand, indices like FTSE 100, NIKKEI 225, NASDAQ 100, SSE 50, DAX, HENG SENG, MOEX.ME and SENSEX have shown a negative percentage change. Moreover, Global stock markets have posted the biggest fall since the 2008 financial crises. It was recommended that future researchers should conduct different stock indices and sample period, the impact of COVID-19 on economic factors like GDP, inflation, interest rate, and effects of COVID-19 on credit markets
Keywords: G32; G01; G15; G19; 330; Response; financial market indices; COVID-19; pandemic; China